2014
DOI: 10.1021/ph4001185
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Selective and Angle-Independent Backscattering from Magnetite Nanoparticle-Decorated Diatom Frustules

Abstract: Periodic heterogeneous structures exhibit color with brilliance through constructive interference of electromagnetic waves in accordance with Bragg's law. However, the wavelength of diffracted light is strictly angle-dependent, and such periodic structures generate only iridescent color. Here we report that periodically porous, microellipsoidal shells of diatom Pinnularia sp. wavelength-selectively backscatter light at arbitrary incidence. The biosilica frustules could be approximated as many polygonal faces o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Diatoms are unicellular marine organisms that have porous biosilica cell walls with dimensions on the order of 10 microns. The porous nature of the diatom frustule gives it roughly 11× more surface area than the glass surface (see File S1, Supporting Information) while the two‐dimensional periodic nanosized pores endow it with hierarchical nanoscale photonic crystal features . We have previously shown the evaporation‐based ability of diatoms to concentrate analytes .…”
Section: Introductionmentioning
confidence: 99%
“…Diatoms are unicellular marine organisms that have porous biosilica cell walls with dimensions on the order of 10 microns. The porous nature of the diatom frustule gives it roughly 11× more surface area than the glass surface (see File S1, Supporting Information) while the two‐dimensional periodic nanosized pores endow it with hierarchical nanoscale photonic crystal features . We have previously shown the evaporation‐based ability of diatoms to concentrate analytes .…”
Section: Introductionmentioning
confidence: 99%
“…Jiao et al demonstrated the magnetite nanoparticle modification of diatom ( Pinnularia sp.) hybrids with short‐range periodicity and long‐range isotropy served as angle‐independent near‐infrared reflectors . These research may inspire future development of broadband infrared reflectors for potential applications as smart windows…”
Section: Solar Energy Reflectionmentioning
confidence: 95%
“…[57] Diatoms are even more specialized than coccolithophores in photonic control by silica structures, and hence diatom bare frustules have been investigated as natural micro-lenses, optical filters, polarizers, waveguides, [58] beam splitters, couplers, laser cavities and angle-independent near-infrared reflectors. [59] Among diatom species, Coscinodiscus has been extensively investigated for photonic properties related to its frustule [74] ; (c) fluorescence microscopy image of luminescent stained biosilica in living diatoms, with permission. Bar: 30 µm [75] ; (d 1-4 ) cathodoluminescence emission of doped coccoliths and SEM image of Tb 3+ -doped coccoliths, with permission of Ref.…”
Section: Photonic and Electronic Applicationsmentioning
confidence: 99%